A farewell to arms - Hemingway, Ernest (Penguin, 1970)
By turns romantic and harshly realistic, Hemingway's story of a tragic romance set against the brutality and confusion of World War I cemented his fame as a stylist and as a writer of extraordinary literary power. A volunteer ambulance driver and a beautiful English nurse fall in love when he is wounded on the Italian front. The best American novel to emerge from World War I, A Farewell to Arms is the unforgettable story of an American ambulance driver on the Italian front and his passion for a beautiful English nurse. Hemingway's frank portrayal of the love between Lieutenant Henry and Catherine Barkley, caught in the inexorable sweep of war, glows with an intensity unrivaled in modern literature, while his description of the German attack on Caporetto -- of lines of fired men marching in the rain, hungry, weary, and demoralized -- is one of the greatest moments in literary history. A story of love and pain, of loyalty and desertion, A Farewell to Arms, written when he was 30 years old, represents a new romanticism for Hemingway